Reproductive Risk Estimation Calculator for Balanced Translocation Carriers. Issue 12 (26th December 2022) - Trunca, Carolyn; Mendell, Nancy R.; Schilit, Samantha L.P.
Abstract: Balanced translocation carriers experience elevated reproductive risks, including pregnancy loss and children with anomalies due to generating chromosomally unbalanced gametes. While understanding the likelihood of producing unbalanced conceptuses is critical for individuals to make reproductive decisions, risk estimates are difficult to obtain as most balanced translocations are unique. To improve reproductive risk estimates, Drs. Trunca and Mendell created models based on a logistic regression analysis of a dataset of over 6000 individuals from over 1000 translocation families. While risk assessments using these models have been offered as a free service for years, this protocol aims to create a sustainable model for genetics professionals to obtain risk estimates for their patients directly. This protocol guides the user through collecting clinical information, using a risk‐generating Java program based on the models, and interpreting the program outputs. A practice tutorial is provided to ensure competency in interpretation prior to use. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Estimation of reproductive risks for balanced translocation carriers Basic Protocol 2 : Practical examples of typical patient encounters with instructive interpretations